2018
DOI: 10.1016/j.jfda.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress evoked damages leading to attenuated memory and inhibition of NMDAR–CaMKII–ERK/CREB signalling on consumption of aspartame in rat model

Abstract: Many controversial reports are available on the use of aspartame as it releases methanol as one of its metabolite during metabolism. The present study proposes to investigate whether long term (90 days) aspartame (40 mg/kg b.wt) administration could induce oxidative stress and alter the memory in Wistar strain male albino rats. To mimic the human methanol metabolism, methotrexate (MTX)-treated rats were included as a model to study the effects of aspartame. Wistar strain albino rats were administered with aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Emerging evidence has shown that high-potency sweeteners could induce oxidative stress in mammals ( Simintzi et al., 2007 , Erbaş et al., 2018 , Iyaswamy et al., 2018 ). To evaluate whether sweeteners used in the present study could cause oxidative stress in the jejunum of broiler chickens, the antioxidant capacity and MDA content in the jejunal mucosae were determined.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that high-potency sweeteners could induce oxidative stress in mammals ( Simintzi et al., 2007 , Erbaş et al., 2018 , Iyaswamy et al., 2018 ). To evaluate whether sweeteners used in the present study could cause oxidative stress in the jejunum of broiler chickens, the antioxidant capacity and MDA content in the jejunal mucosae were determined.…”
Section: Discussionmentioning
confidence: 99%
“…In cell signalling, nitrosative and oxidative stress are located upstream of the apoptotic and the survival biomarkers caspas-3 and Bcl-2 upon activation in many cases such as tissue injury (Iyaswamy et al, 2018;Liang & Su, 2019). Our data that points to the induction of brain tissue injury, nitrosative and oxidative stress, and inhibition of SOD and Bcl-2 by CUS Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Aspartame is metabolized in the body to methanol which can be detected even after 24 hr of exposure. Methanol is primarily metabolized by oxidation to formaldehyde and then to formic acid which induce increased production of free radicals and increased oxidative damage in multiple tissues and may be responsible for the formation of superoxide anion and hydrogen peroxide (Humphries, Pretorius, & Naudé, 2008) and (Iyaswamy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%